2017
DOI: 10.5194/bg-14-3461-2017
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of trees and understory plants to nitrogen fertilization in a subtropical forest in China

Abstract: Abstract. Reactive nitrogen (N) increase in the biosphere has been a noteworthy aspect of global change, producing considerable ecological effects on the functioning and dynamics of the terrestrial ecosystems. A number of observational studies have explored responses of plants to experimentally simulated N enrichment in boreal and temperate forests. Here we investigate how the dominant trees and different understory plants respond to experimental N enrichment in a subtropical forest in China. We conducted a 3.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 37 publications
0
10
1
2
Order By: Relevance
“…Increased N availability would promote plant growth, while excess N would have opposite effect due to soil acidification, nutrient imbalance and competition with fast‐growing species (Dirnboeck et al., 2018; Lu et al., 2014; Mao et al, 2018; Tian et al., 2017). As mentioned earlier, because of the biological and physical processes in the canopy (Houle et al., 2015; Wortman et al., 2012), N inputs into the forest floor are less with CAN than with UAN, suggesting that UAN is more likely than CAN to inhibit plant growth (Mao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Increased N availability would promote plant growth, while excess N would have opposite effect due to soil acidification, nutrient imbalance and competition with fast‐growing species (Dirnboeck et al., 2018; Lu et al., 2014; Mao et al, 2018; Tian et al., 2017). As mentioned earlier, because of the biological and physical processes in the canopy (Houle et al., 2015; Wortman et al., 2012), N inputs into the forest floor are less with CAN than with UAN, suggesting that UAN is more likely than CAN to inhibit plant growth (Mao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The N cycle is very important for forest ecosystems, and the soil N mineralization rate is often used as an index of soil N availability and loss (Tian et al 2017;Liu et al 2017a, b, c). Consistent with the results of most previously published studies (Sardans and Peñuelas 2012), in the present study, N mineralization rate was significantly affected by N addition practices (Fig.…”
Section: Effect Of N Addition In Different Seasons On N Dynamicsmentioning
confidence: 99%
“…Excessive N addition contributes to soil acidification (Tian and Niu 2015), which may have a suite of negative effects such as shifts from N to P limitation (Huang et al 2016), nitrous oxide emissions Yu et al 2017), and considerable NO 3 − leaching from soils (Lovett and Goodale 2011;Huang et al 2016). Tian et al (2017) showed that the plot-averaged absolute and relative growth rates of basal area and aboveground biomass were not affected by N addition in a Castanopsis eyrei subtropical forest. Janssens et al (2010) demonstrated that N addition reduces the distribution of plant photosynthetic products to roots and reduces their activity (Mo et al 2007(Mo et al , 2008Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the local environment can change the quality and condition of trees, and this can be evaluated through variables that express the vigor of vegetative structures [4]. According to Tian et al (2017) [5], the analysis of visible external conditions of trees may reflect the quality of their internal structure. Thus, trees that express low external quality can have internal conditions also compromised.…”
Section: Sivaskomentioning
confidence: 99%
“…In the long term, the addition of nitrogen may support the phosphorus release in the soil, since this process induces the development of the solubilizing bacteria of inorganic phosphate in the soil [32]. In contrast, in a study about the effects of nitrogen fertilization, Tian et al (2017) [5] observed that an excessive dosage of nitrogen could reduce the phosphorus absorption, due to the competition for the active sites in the rhizosphere. However, in order to promote the best effect with fertilization, especially in the case of established urban trees, they must be exposed to an adequate amount of water, aiming at the balance of photosynthetic and physiological processes [9].…”
Section: Vegetative Vigormentioning
confidence: 99%